Education Thought Imam Zarnuji and Paulo Freire: An Synthesis Analysis - Moch Tolchah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Keywords: Synthesis Analysis, Zarnuji education thinking, Paulo Freire education thinkingThis research focuses on several issues as follows: first, how is the concept of education according to Imam Zarnuji; second, what is the concept of education according to Paulo Freire; Third, how is the comparison between Imam Zarnuji and Paulo Freire's education, and can both be synthesized towards Qur'ani educationThe concept of education offered by Zarnuji and Freire can be said as a representation of Islamic and Western education, both of which have sides of equality and there are sides of difference; there are strong sides and weak sides. There should be an effort to evaluate proportionally between Islamic and Western education, then sorting and choosing between the two; and those which are still relevant to the times, need to be synthesized (combined) towards the ideal educational concept.On the one hand, Western education (the concept of Freire) strongly emphasizes aspects of